Direct conversion of methane to formic acid over Au-Fe-NaZSM-5 at ambient pressure using H2O2 - Kumar, Pawan; Ahangar, Iqra; Kesarwani, Srishti; Urkude, Rajashri; Patil, Nita A. R.; Niphadkar, Prashant; Bokade, Vijay V.; Haider, M. Ali; Vinod, C. P. (Catalysis Science & Technology, 2026)
Direct conversion of methane to value-added products is a long-standing challenge. This report presents the one-step conversion of methane to oxygenates using H2O2 as an oxidant over an Au and Fe supported on NaZSM-5 (0.1Au0.1FeNZ) catalyst, which produces 4264 mu mol of oxygenates with 89% selectivity toward formic acid at 10 bar and 60 degrees C within 30 min in a batch process. The catalyst also produces 26.5 mu mol of oxygenates with 70% selectivity for formic acid at atmospheric pressure and 80 degrees C in a continuous flow process over 9 h of reaction time, making it the first report of such a process. The synergistic interaction of Au and Fe, with the crucial role of Na ions in the zeolite framework in driving the reaction, is revealed through various characterization tools like TEM, XPS, and XAS. Theoretical studies elucidate the active sites responsible for lowering the activation barrier for the crucial C-H activation step. Thus, the catalyst enables the conversion of methane into formic acid with high activity and selectivity, offering new possibilities for harnessing this potent greenhouse gas under process-friendly conditions that were previously unexplored.

Selectivity reversal from CO to ethylene products in CO2 photoreduction via electronic modulation of SnS2 using a vinyl-bridged porous organic polymer - Chakraborty, Subhajit; Boro, Bishal; Navodye, S. A. Keishana; Ghosh, Rajib; Shrotri, Abhijit; Urkude, Rajashri; Chawla, Geetansh; Vinod, C. P.; Gunasooriya, G. T. Kasun Kalhara; Mondal, John; Peter, Sebastian C. (Journal of the American Chemical Society, 2026)
Developing an efficient and robust photocatalyst for optimal C2+ product generation from carbon dioxide (CO2) is a pressing need in advancing solar fuel production. In this study, we designed an ionic vinylene-bridged conjugated porous organic polymer (Py-POP) enriched with charged pyridine groups via a quaternization-promoted Knoevenagel condensation reaction. The resulting positively charged polymeric framework with shape-persistent nanochannels enabled the uniform assembly of SnS2 units through ionic interactions mediated by amino and sulfhydryl groups. The hybrid porous photopolymer (SnS2@Py-POP) converts CO2 into ethylene with a rate of 34.7 mu mol g-1 h-1 with a selectivity of ethylene around 78.7% under visible light photoirradiation, which outperforms all the C2 selective Sn-based photocatalysts. Our findings principally sheds light on the mechanism of selectivity reversal (from C1 to C2 product) by hybrid catalyst framework engineering. In-depth investigations by synchrotron-based X-ray absorption spectroscopy (XAS) and morphological analysis via high-resolution transmission electron microscopy (HRTEM) reveal the nature of interaction for hybrid heterostructure formation within the porous network. Electron transfer pathways were mapped using time-resolved photoluminescence (TRPL) and transient absorption spectroscopy (TAS), which revealed a Z-scheme electron transfer mechanism. This mechanism facilitates enhanced electron accumulation on the SnS2 layer, promoting efficient CO2 activation and subsequent C-C coupling, ultimately leading to ethylene formation. Furthermore, the ethylene formation mechanism has been investigated in detail by time-resolved diffuse reflectance infrared spectroscopy (TR-DRIFTS), corroborated with density functional theory (DFT). This study opens a new avenue for achieving selectivity reversal in a C1 selective photocatalyst through electronic modulation enabled by the formation of an inorganic-organic hybrid heterostructure.